Proposing a Model of Organizational Inertia Management in Iranian Public Organizations - Nourinejad Largani , Khadijeh; Kia Kojouri, Davood; Hajiaghajani, Azam; Rahmaty, Maryam (Future of Work and Digital Management Journal, 2025)
This study was conducted with the aim of designing a model for managing organizational inertia in Iranian public organizations using a meta-synthesis and Delphi approach. In the meta-synthesis stage, domestic and international studies related to organizational inertia and its management were extracted from reputable databases and analyzed through a meta-synthesis method. After screening the extracted articles, 49 international and 17 domestic studies were selected for coding. In the second stage, the results were refined through the Delphi technique, in which the sample consisted of 10 academic and organizational experts who were familiar with organizational inertia management, had authored publications in the field, possessed more than 20 years of professional experience, and held managerial positions. Model collection and representation were conducted using MAXQDA software. After integrating and finalizing the findings from the meta-synthesis and Delphi analyses, the results identified five overarching criteria (strong and transformational leadership, transparent communication and active employee participation, fostering an adaptive and learning-oriented organizational culture, strategic redesign of organizational structures and resources, and development of preventive support systems) and 16 components (transformational leadership, paradoxical leadership, empowering leadership, transparent communication, active employee participation, fostering acceptance of change and flexibility, promoting continuous learning and knowledge sharing, fostering innovation and creativity, building psychological safety and trust, developing flexible and resilient environments, alignment of leadership, values and identity, redesigning organizational structure, reallocation and reconstruction of resources, adaptation of human resource practices and roles, training programs and skill development, and incentive and reward systems). The proposed model, by integrating the findings of meta-synthesis and the Delphi technique, provided a comprehensive framework that emphasizes the necessity of identifying the indicators of organizational inertia management in Iranian public organizations.